United Arab Emirates (International Monetary Fund, 2022)
A swift policy response helped mitigate the economic impact of the twin COVID-19 and oil price shocks and contain the initial spread of the virus. A gradual recovery driven by the non-oil sector is underway, following a deep recession in 2020. Fiscal and external balances have improved with recent oil price increases. The UAE is among the world leaders in delivering vaccinations, with nearly 85 percent of the population fully vaccinated as of October 2021
10.5089/9798400202834.002
Keywords: Graue Literatur; manufacturing sector producer price index; reform effort; CPI data; CPI basket weight; Policy discussion; liability positions vis-à-vis nonresident; Global; Oil prices; Loans; Financial sector stability; International Agreements and Observance; International Organizations; Monetary Policy; Finance: General; Industries: Financial Services; Statistics; Fiscal Policy; National Government Expenditures and Related Policies: General; Energy: Demand and Supply; Data Collection and Data Estimation Methodology; Computer Programs: Other; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Monetary economics; International institutions; Macroeconomics; Public finance & taxation; Finance; Econometrics & economic statistics; Economic growth; International organization; Expenditure; Money and Monetary Policy; International Economics; Financial institutions; Public Finance; Financial sector policy and analysis; Monetary policy; International agencies; Fiscal policy; Expenditures; Public; Prices; Finance; Statistics